Optimum splitting ratio for amplifier noise reduction by an asymmetric nonlinear optical loop mirror - Meißner, Markus; Rösch, Matthias; Schmauß, Bernhard; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2005)
We theoretically and experimentally analyze the influence of the splitting ratio and the input power on the noise reduction capability of an asymmetric nonlinear optical loop mirror (NOLM) for different input noise levels. An easy method to calculate the optimum parameters for noise reduction is also presented. The best noise reduction is found at NOLM input powers at which the nonlinear transfer function has a slope close to zero. Additionally, the splitting ratio of the NOLM has to be adapted to its input noise level to suppress amplitude fluctuations effectively. Since the noise reduction by the NOLM is due to the Kerr nonlinearity, which has a timescale below a few femtoseconds, the noise reduction is applicable to short pulses in the picosecond and femtosecond range. This makes the NOLM applicable as an optical regenerator in an optical data transmission system at high bit rates, such as 160 GBit/s. © Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.optimu